Valorized chicken feather as corrosion inhibitor for mild steel in drilling mud (2019)
Modified chicken feather reduced the corrosion rate of mild steel in drilling mud as deduced from electrochemical potentiodynamic polarization technique, albeit, with observed infestation of the test environment by microbes over protracted exposure period of 92 days. The corrosion rates with and without the addition of 0.3g of hydrolyzed feather per 100 ml of drilling mud were 1.70 and 1.95 mm/yr, respectively; which corresponded to inhibition efficiency of 13% over the immersion period. The corresponding charge transfer resistances, a measure of corrosion rates were 1480.4 and 1780.0 Ω, respectively; in the uninhibited and hydrolyzed-feather inhibited environments. The voltage over the double layer capacitor as obtained from the polarization studies numerical increased from -0.907 to -0.948 V which indicated adsorption of moieties in the inhibitor and probably some corrosion products on the surface of the mild steel specimen.